Body Mass Index Best Predicts Recovery of Recombinant Factor VIII in Underweight to Obese Patients with Severe Haemophilia A - Tiede, Andreas; Cid, Ana Rosa; Goldmann, Georg; Jiménez-Yuste, Victor; Pluta, Michael; Lissitchkov, Toshko; May, Marcus; Matytsina, Irina; Miljic, Predrag; Pabinger, Ingrid; Persson, Paula (Thrombosis and Haemostasis, 2020)
Background Factor VIII (FVIII) products are usually dosed according to body weight (BW). This may lead to under- or over-dosing in underweight or obese patients, respectively.Objective This article evaluates the pharmacokinetics (PK) of recombinant FVIII concentrate, particularly recovery, in relation to body mass index (BMI) and other body composition descriptors.Materials and Methods Thirty-five previously treated adults with severe haemophilia A from five BMI categories (underweight, normal, overweight, obese class I and II/III) were included. PK was evaluated after 50 IU per kilogram of BW single-dose recombinant FVIII (turoctocog alfa). The body composition variable was based on measurements of weight, height, bioimpedance analysis, and dual-energy X-ray absorptiometry. A dosing model was derived to achieve similar peak FVIII activity levels across BMI categories.Results A statistically significant positive association between BMI and C30min, IR30min, and AUC0–inf was observed; CL and Vss showed a significant negative association with BMI; t½ was independent of BMI and other parameters. The dosing model introduced a correction factor ‘M’ for each BMI category, based on linear regression analysis of C30min against BMI, which ranged from 0.55 for underweight to 0.39 for obese class II/III. This model achieved similar peak FVIII activity levels across BMI categories, estimating an average dose adjustment of +243.3 IU (underweight) to –1,489.6 IU (obese class II/III) to achieve similar C30min.Conclusion BMI appears to be the best predictor of recombinant FVIII recovery; however, PK endpoints were also dependent on other body composition variables. The model demonstrated that dosing can be adjusted for individual BMI to achieve better FVIII predictability across BMI categories.
Keywords: body mass index; dosing model; recombinant factor VIII; haemophilia; pharmacokinetics